Kebijakan Perpajakan di Indonesia untuk Kemudahan Ekonomi saat Masa Pandemi Covid-19 - Tambunan, Maria R.U.D. (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2020)
This research is aimed at discussing various policies on providing tax incentives offered by the Indonesian government to reduce the economic uncertainty impact caused by the pressure caused by the co-19 pandemi. In implementing tax incentives, the facilities provided by the government are in the form of easing administrative obligations and cutting the amount of tax obligations should be paid by individual taxpayers and corporate taxpayers. In addition to taxation policies in Indonesia, this study also discusses policies implemented by the Austrian government. Austria is the first European Union member country which has been ease the locked down and also the country has been implementing tax incentive policies as a social economic instrument. This study uses a qualitative approach with qualitative research methods. Data occupied for this research was collected through literature study, documentation study and limited discussion. This study explains that the policies implemented by using taxation instruments generally have been inline with international trends, adjusted to the ability of the state. The instruments offered in the form of administrative ease, temporary tax burden cuts to the reduction in corporate income tax rates that will be implemented until the next few years. It is expected that these various policies can withstand economic pressures due to the current pandemi. However, on the other hand, the other important thing from the redistribution of these incentives is the supervision, the transparency on the benefit redistribution and reporting on the use of incentives provided.